One Year of Seismicity Recorded Through Ocean Bottom Seismometers Illuminates Active Tectonic Structures in the Ionian Sea (Central Mediterranean) - Sgroi, Tiziana; Polonia, Alina; Beranzoli, Laura; Billi, Andrea; Bosman, Alessandro; Costanza, Antonio; Cuffaro, Marco; D’Anna, Giuseppe; De Caro, Mariagrazia; Di Nezza, Maria; Fertitta, Gioacchino; Frugoni, Francesco; et al. (Frontiers in Earth Science, 2021)
Seismological data recorded in the Ionian Sea by a network of seven Ocean Bottom Seismometers (OBS) during the 2017-2018 SEISMOFAULTS experiment, provides a close-up view of seismogenic structures that are potential sources of medium-high magnitude earthquakes. The high-quality signal-to-noise ratio waveform are observed for earthquakes at different scales: teleseismic, regional, and local earthquakes as well as very local and crack events. We focus on two different types of recording: (1) local and very local earthquakes and (2) Short Duration Events (SDE) associated to microfracturing processes. During the SEISMOFAULTS experiment, 133 local earthquakes were recorded by both OBSs and land stations, while very local earthquakes (116), due to their low magnitude, were recorded only by the OBS network. We relocated 133 local earthquakes by integrating onshore and offshore travel times and obtaining a significant improvement in accuracy, particularly for the offshore events. Moreover, the higher signal-to-noise ratio of the OBS network revealed a significant seismicity not detected onshore, which shed new light on the location and kinematics of seismogenic structures in the Calabrian Arc accretionary prism and associated to the subduction of the Ionian lithosphere beneath the Apennines. Other signals recorded only by the OBS network include a high number of Short Duration Events (SDE). The different waveforms of SDEs at two groups of OBSs and the strict correlation between the occurrence of very local events and SDEs, suggest an endogenous fluid venting form mud volcanoes and active faults traces. Results from the analysis of seismological data collected during the SEISMOFAULTS experiment confirms necessity and potential of marine studies with OBSs, particularly in geologically active areas of the Mediterranean Sea prone to high seismic risk.